Trade Policy Instruments over Time - Bown, Chad P. (World Bank, Washington, DC, 2014)
This paper surveys political-economic research on the variety of instruments that governments use to conduct international trade policy. It presents key insights on the relationships between instruments such as tariffs, quotas, voluntary export restraints, and other nontariff barriers, as well as the ebb and flow of the national use of temporary trade barriers such as antidumping, countervailing duties, and safeguards. The survey examines trends in use of these trade policy instruments over recent history; and it reviews the major theoretical and empirical explanations behind, and interrelationships between, their uses. Finally, the paper highlights potential institutional impacts of the General Agreement on Tariffs and Trade (GATT) and subsequent World Trade Organization (WTO) on choice of policy instruments, as well as how multilateral, unilateral, and preferential tariff liberalization may introduce political-economic shocks and affect incentives over time for how governments rely on different instruments.